Perioperative circulating tumor DNA as a potential prognostic marker for operable stage I to IIIA non–small cell lung cancer - Li, Ning; Wang, Bao‐Xiao; Li, Jian; Shao, Yang; Li, Ming‐Tian; Li, Jian‐Jun; Kuang, Peng‐Peng; Liu, Zui; Sun, Tian‐Yu; Wu, Hui‐Qi; Ou, Wei; Wang, Si‐Yu (Cancer, 2022)
Background Circulating tumor DNA (ctDNA) has emerged as a noninvasive biomarker for dynamically monitoring tumors. However, published data on perioperative ctDNA in patients with operable non–small cell lung cancer (NSCLC) are currently limited. Methods This prospective study recruited 123 patients with resectable stage I to IIIA NSCLC. Preoperative and postoperative plasma samples and tumor tissue samples were subjected to next‐generation sequencing with a panel of 425 cancer‐related genes. Peripheral blood samples were collected before surgery, postoperatively within 1 month, and every 3 to 6 months for up to 3 years. Results After 4 exclusions, 119 eligible patients were enrolled from June 2016 to February 2019. Presurgical ctDNA was detectable in 29 of 117 patients (24.8%) and was associated with inferior recurrence‐free survival (RFS; hazard ratio [HR], 2.42; 95% CI, 1.11‐5.27; P = .022) and inferior overall survival (OS; HR, 5.54; 95% CI, 1.01‐30.35; P = .026). Similarly, ctDNA was detected in 12 of 116 first postsurgical samples (10.3%) and was associated with shorter RFS (HR, 3.04; 95% CI, 1.22‐7.58; P = .012). During surveillance after surgery, longitudinal ctDNA–positive patients (37 of 119; 31.1%) had significantly shorter RFS (HR, 3.46; 95% CI, 1.59‐7.55; P < .001) and significantly shorter OS (HR, 9.99; 95% CI, 1.17‐85.78; P = .010) in comparison with longitudinal ctDNA–negative patients. Serial ctDNA detection preceded radiologic disease recurrence by a median lead time of 8.71 months. Conclusions These results suggest that perioperative ctDNA analyses can predict recurrence and survival, and serial ctDNA analyses can identify disease recurrence/metastasis earlier than routine radiologic imaging in patients with resectable NSCLC. Lay Summary The utility of serial circulating tumor DNA (ctDNA) monitoring for predicting disease recurrence and survival for early‐stage non–small cell lung cancer (NSCLC) has not been well characterized. The detection of ctDNA before and after surgery is associated with the identification of a high risk of disease recurrence and long‐term patient outcomes for resectable NSCLC. Perioperative ctDNA analyses identify disease recurrence earlier than routine radiologic imaging. ctDNA analyses can detect minimal residual disease for resectable NSCLC and thus can facilitate early intervention. Perioperative circulating tumor DNA (ctDNA) analyses identify disease recurrence earlier than routine radiologic imaging. ctDNA analyses can detect minimal residual disease for resectable non–small cell lung cancer and thus can facilitate early intervention.